A STUDY ON THE EPIDEMIOLOGICAL CHARACTERISTICS OF OVERWEIGHT AND OBESITY AND ITS RELATIONSHIP WITH THE HYPERTENSION AMONG ADULT RESIDENTS IN SHANDONG PROVINCE. (8th October 2012) - Jing, Dong; Xiaolei, Guo; Jiyu, Zhang; Junli, Tang; Zilong, Lu; Jie, Chu; Aiqiang, Xu
Abstract : Objectives: To describe the epidemiological distribution of overweight and obesity and explore its relationship with hypertension among adult residents in Shandong province. Methods: A cross-sectional survey was conducted among 15 350 permanent residents aged between 18–69 years old with stratified multistage sampling during July to August 2011, in Shandong province. All participants were interviewed with a standard questionnaire. Anthropometric indicators including height, weight and waist circumference (WC) were measured. Results: The general prevalence rate of overweight, obesity and central obesity was 32.77%, 16.60% and 50.33% among adult residents in Shandong province. There is no difference of the epidemiological distribution between different groups classified by gender, region and city. The average levels of blood pressure gradually increased with the increasing of BMI and WC, while the rate of hypertension also increased. The prevalence rate of hypertension was 8.56%, 13.42% and 28.20% among normal BMI, overweight and obesity people. After adjusting age and gender, the prevalence rates were 2.34 times and 5.92 times higher among overweight and obesity people than those among normal BMI people. Conclusions: Nearly half of Shandong adult residents are overweight or obesity. Overweight and obesity have become important public health problems in Shandong province and they are major risk factors to cause hypertension. Health education and health promotion should be strengthened to prevent and control overweight and obesity.